Less safety for more efficiency: water relations and hydraulics of the invasive tree Ailanthus altissima (Mill.) Swingle compared with native Fraxinus ornus L. (3rd July 2018) - Petruzzellis, Francesco; Nardini, Andrea; Savi, Tadeja; Tonet, Vanessa; Castello, Miris; Bacaro, Giovanni
Abstract: Invasion of natural habitats by alien trees is a threat to forest conservation. Our understanding of fundamental ecophysiological mechanisms promoting plant invasions is still limited, and hydraulic and water relation traits have been only seldom included in studies comparing native and invasive trees. We compared several leaf and wood functional and mechanistic traits in co-occurring Ailanthus altissima (Mill.) Swingle (Aa) and Fraxinus ornus L. (Fo). Aa is one of the most invasive woody species in Europe and North America, currently outcompeting several native trees including Fo. We aimed at quantifying inter-specific differences in terms of: (i) performance in resource use and acquisition; (ii) hydraulic efficiency and safety; (iii) carbon costs associated to leaf and wood construction; and (iv) plasticity of functional and mechanistic traits in response to light availability. Traits related to leaf and wood construction and drought resistance significantly differed between the two species. Fo sustained higher structural costs than Aa, but was more resistant to drought. The lower resistance to drought stress of Aa was counterbalanced by higher water transport efficiency, but possibly required mechanisms of resilience to drought-induced hydraulic damage. Larger phenotypic plasticity of Aa in response to light availability could also promote the invasive potential of the species.